InlP, a New Virulence Factor with Strong Placental Tropism - Cristina Faralla; Gabrielle Rizzuto; David Lowe; Byoungkwan Kim; Cara L. Cooke; Lawrence R. Shiow; Anna I. Bakardjiev (2016)
Intrauterine infection is a major detriment for maternal-child health and occurs despite local mechanisms that protect the maternal-fetal interface from a wide variety of pathogens. The bacterial pathogen Listeria monocytogenes causes spontaneous abortion, stillbirth, and preterm labor in humans and serves as a model for placental pathogenesis. Given the unique immunological environment of the maternal-fetal interface, we hypothesized that virulence determinants with placental tropism are required for infection of this tissue. We performed a genomic screen in pregnant guinea pigs that led to the identification of 201 listerial genes important for infection of the placenta but not maternal liver. Among these genes was lmrg1778 (lmo2470), here named inlP, predicted to encode a secreted protein that belongs to the internalin family. InlP is conserved in virulent L. monocytogenes strains but absent in Listeria species that are nonpathogenic for humans. The intracellular life cycle of L. monocytogenes deficient in inlP (ΔinlP) was not impaired. In guinea pigs and mice, InlP increased the placental bacterial burden by a factor of 3 log10 while having only a minor role in other maternal organs. Furthermore, the ΔinlP strain was attenuated in intracellular growth in primary human placental organ cultures and trophoblasts. InlP is a novel virulence factor for listeriosis with a strong tropism for the placenta. This virulence factor represents a tool for the development of new modalities to prevent and treat infection-related pregnancy complications.